Regional Upgrading in Southern Europe Spatial Disparities and Human Capital - Fonseca, Madalena; Fratesi, Ugo (Advances in Spatial Science, The Regional Science Series, 2017)
XIX, 358 p. 74 illus., 12 illus. in color.